Decoding the EU's most threatening criminal networks (Publications Office of the European Union, 2024)
This report distils a wealth of information on 821 criminal networks active in the EU, gathered by Europol in the context of our regular support to criminal investigations. It is also based on a targeted data collection effort, which has granted us an unprecedented intelligence picture. Its findings represent the most detailed contemporary study on the most threatening criminal networks ever undertaken by the European law enforcement community. This report decodes the ABCD of the most threatening criminal networks and assesses what makes these networks most threatening - they are Agile, Borderless, Controlling and Destructive. This analysis of over 800 criminal networks lays the foundations for tackling and disrupting their operations. Investigating and bringing them to justice is a goal that can only be achieved through a culture of police cooperation across Europe and beyond. With this first analysis, Europol and our partners make the invisible visible and decode the inner workings of criminal networks.